THE POETICS OF LATER GREEK ECPHRASIS: CHRISTODORUS COPTUS, THE PALATINE ANTHOLOGY AND THE PERIOCHAE OF NONNUS' DIONYSIACA. (December 2018) - Middleton, Fran
Abstract : There is increasing interest in what might be thought 'special' about late antique poetry. Two volumes of recent years have focused on Latin poetry of this time, Classics Renewed: Reception and Innovation in the Latin Poetry of Late Antiquity edited by Scott McGill and Joseph Pucci (2016) as well as The Poetics of Late Latin Literature edited by Jaś Elsner and Jesús Hernández Lobato (2017), while it has become increasingly acceptable to remark on late antiquity as a cultural period in its own right, rather than a point of transition between high antiquity and the middle ages. Greek poetry of late antiquity has yet to receive the level of attention offered to Latin literature of this time, and so it is to help answer the question of what may be thought special about late antique Greek poetry that I here discuss the poetics of later Greek ecphrasis.